The Role of Technology Use to Overcome Misconception in Physics Learning: A Systematic Literature Review - Fahmi Yahya; Andi Haris; Satri Asriyanti; Hermansyah Hermansyah (Indonesian Journal of Teacher Education, 2026)
Misconceptions are persistent cognitive barriers in physics learning because physics concepts are abstract and often contradict students' everyday intuition. This systematic literature review aims to identify, evaluate, and synthesize empirical evidence regarding the role of technology use in addressing misconceptions in physics learning during the 2015–2025 period. Systematic searches were conducted across Scopus, IEEE Xplore, and Google Scholar databases. A total of 41 primary studies met the inclusion criteria and were synthesized using a narrative-thematic approach. Five technology categories were identified as dominant remediation strategies: PhET interactive simulations, virtual laboratories, augmented reality/virtual reality, multimedia and educational games, and computer-assisted conceptual learning models. The majority of studies reported consistent decreases in misconception rates and improvements in conceptual understanding following interventions. PhET simulations remained the most widely researched technology, while research trends during 2022–2025 showed a marked increase in immersive AR/VR studies. Technology functions as a tool for visualizing abstract concepts and facilitating cognitive conflict that drives conceptual change.